2008
DOI: 10.1167/8.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Early correlates of visual awareness in the human brain: Time and place from event-related brain potentials

Abstract: When something appears, how soon is the first neural correlate of awareness of it, and where is that activity in the brain? To answer these questions, we measured the electroencephalogram under conditions in which visual stimuli changed identically but in which awareness differed. We manipulated awareness by using binocular rivalry between orthogonal gratings viewed one to each eye. Then we changed the orientation of the grating to one eye to be the same as that to the other eye. Because of the rivalry, someti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
33
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 54 publications
16
33
1
1
Order By: Relevance
“…Thus, the change in awareness was associated with early negativity, similar to VAN, followed by later positivity (LP). Further studies have revealed the same pattern with the addition that changes have elicited also an early positive enhancement in P1 range (Roeber and Schrö ger, 2004;Roeber et al, 2008;Veser et al, 2008).…”
Section: Bistable Perceptionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the change in awareness was associated with early negativity, similar to VAN, followed by later positivity (LP). Further studies have revealed the same pattern with the addition that changes have elicited also an early positive enhancement in P1 range (Roeber and Schrö ger, 2004;Roeber et al, 2008;Veser et al, 2008).…”
Section: Bistable Perceptionmentioning
confidence: 59%
“…The early awareness-related enhancement of P1 emerges in response to reduced contrast stimuli (Pins and ffytche, 2003;Wilenius and Revonsuo, 2007), change detection (Busch et al, in press;Pourtois et al, 2006) or during perception of bistable stimuli, that is, during binocular rivalry (Roeber and Schrö ger, 2004;Roeber et al, 2008;Veser et al, 2008) or the perception of a Necker lattice Bach, 2005, 2006). Also a MEG study (Boehler et al, 2008) found a difference between effectively vs. ineffectively masked stimuli in the P1 time window around 100 ms.…”
Section: Summary and Conclusion From The Erp Findingsmentioning
confidence: 99%
“…For example, Valle-Inclan et al (1999) found that stimuli presented to the dominant eye elicited higher ERP responses compared to stimuli presented to the suppressed eye under rivalrous conditions. Their percept-dependent ERP effects started at 70 ms from stimulus onset (see also Roeber et al, 2008;Veser, O'Shea, Schroger, Trujillo-Barreto, & Roeber, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested either early (ϳ100 ms) (Pins and Ffytche, 2003;Roeber et al, 2008) or late (ϳ300 ms) (Sergent et al, 2005;Del Cul et al, 2007) activity correlated with visibility. Our results, however, suggest that the signatures of visibility are not bound to processes with a strict latency but depend on the presence of expectations (Banquet and Grossberg, 1987).…”
Section: Signatures Of Visibility: Early or Late?mentioning
confidence: 93%